An Indian Ocean precursor for Indian summer monsoon rainfall variability. Issue 21 (11th November 2015) - Sreejith, O. P.; Panickal, S.; Pai, S.; Rajeevan, M.
Abstract: The Indian summer monsoon rainfall (ISMR) depicts large interannual variability strongly linked with El Niño–Southern Oscillation (ENSO). However, many of the El Niño years were not accompanied by deficient ISMR. The results from the study reveal the significant role of coupled air‐sea interaction over the tropical Indian Ocean (IO) in modifying the ENSO‐ISMR association. The IO warm water volume (WWV), a measure of heat content variations in the equatorial IO has strong influence on ISMR. A deepening (shoaling) of thermocline in the eastern equatorial IO (EEIO) during late boreal spring (April–May) accompanied by increase (decrease) in WWV anomalies weaken (enhance) the ISMR by enhancing (suppressing) the convection over EEIO resulting in the below (above) normal ISMR. Thus, the changes in the WWV anomalies in the EEIO along with ENSO conditions during boreal spring can be considered as a precursor for the performance of subsequent ISMR. Key Points: An attempt is made to identify an oceanic parameter having predictive skill for ISMR Role of air‐sea interaction in Indo‐Pacific Ocean provides better understanding of ISMR variability Dominant forcing for interannual variability of ISMR is not known